Enhancing Polish firms' innovation activities in comparison to the other Moderate Innovators countries - Aleksandra Zygmunt (Institute of Economic Research (IER), 2017)
Faced with circumstances of rapid changes, the crucial is stimulation of actions aimed at enhancing competitiveness. In this regard, the European Union strategy Europe 2020 should be mentioned. Concerning the role of firms' innovation activities in economic growth of regions and countries, it is important to explore how enhancing Polish firms' innovation activities differ between the EU countries with a similar to Poland level of innovation. Thus, the particular emphasis was put on the Moderate Innovators countries.The aim of this paper is to investigate enhancing Polish firms' innovation activities against those from the other Moderate Innovators countries.The study was based on data from the European Innovation Scoreboard 2016 related to firm activities dimensions: firm investments, linkage & entrepreneurship and intellectual assets. The time period was 2008-2015 and was limited by data availability. To study multivariate analysis and the zero unitarization methods were applied. These methods allowed to multivariate analysis of enhancing firms' innovation activities in Poland and those from the other EU countries with similar to Poland level of innovation.This paper contributes to the existing literature by providing new insight on understanding the issues related to firms' innovation activities. The results reveal, among others, that although Polish firms' innovation activities have improved against those from the other Moderate Innovators counties, it requires further enhancing. The findings have practical and policy implications. It is assumed that the obtained results may be useful for firms, regions and country in enhancing competitiveness.
Keywords: O30; O52; R11; 330; innovation activities; firm; the European Union; Moderate Innovators countries